Advancements in Stem Cell Applications for Livestock Research: A Review - Limeng Shi; Muhammad Zahoor Khan; Abd Ullah; Huili Liang; Mingyang Geng; Muhammad Faheem Akhtar; Jincheng Na; Ying Han; Changfa Wang (Veterinary Sciences)
Stem cells (SCs), distinguished by their capacity for self-renewal and multipotent differentiation, represent a cornerstone of regenerative medicine. These cells, which can be categorized according to their differentiation potential and developmental origin, have emerged as pivotal elements in both biomedical research and veterinary science. In herbivorous species, stem cell applications have yielded particularly promising advances across multiple domains, including reproductive biotechnology, tissue engineering and regeneration, therapeutic interventions, and immunomodulation. This review synthesizes contemporary research on stem cell biology in five economically significant herbivorous species: bovine, ovine, deer, equine, and camelid. Special emphasis is placed on stem cell isolation methodologies, culture optimization techniques, and the molecular mechanisms governing key signaling pathways. The discussion encompasses both the technical impediments facing stem cell research and the ethical framework necessary for responsible scientific advancement, with particular attention to animal welfare considerations in the development and implementation of stem cell-based technologies.